2016
DOI: 10.1002/oby.21543
|View full text |Cite
|
Sign up to set email alerts
|

Altered lipid partitioning and glucocorticoid availability in CBG‐deficient male mice with diet‐induced obesity

Abstract: Objective: To evaluate how deficiency in corticosteroid-binding globulin (CBG), the specific carrier of glucocorticoids, affects glucocorticoid availability and adipose tissue in obesity. Methods: C57BL/6 (WT) and CBG-deficient (KO) male mice were fed during 12 weeks with standard or hyperlipidic diet (HL). Glucocorticoid availability and metabolic parameters were assessed. Results: Body weight and food intake were increased in KO compared with WT mice fed a standard diet and were similar when fed a HL diet. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 36 publications
2
7
1
Order By: Relevance
“…There is a discrepancy between our reports and those of Petersen et al (28) and Gulfo et al (29), on the levels of free GC measured after stress, when the rise in GC is important. The latter found either no significant differences in free GCs after stress between WT and Cbg KO or increased levels for Cbg KO, whereas we have shown that Cbg KO show a hypoglucocorticoid response to stress compared to WT (31, 32), including after chronic stress (33).…”
Section: Dissecting Metabolic Alterations In Cbg-deficient Mouse Modelscontrasting
confidence: 99%
See 3 more Smart Citations
“…There is a discrepancy between our reports and those of Petersen et al (28) and Gulfo et al (29), on the levels of free GC measured after stress, when the rise in GC is important. The latter found either no significant differences in free GCs after stress between WT and Cbg KO or increased levels for Cbg KO, whereas we have shown that Cbg KO show a hypoglucocorticoid response to stress compared to WT (31, 32), including after chronic stress (33).…”
Section: Dissecting Metabolic Alterations In Cbg-deficient Mouse Modelscontrasting
confidence: 99%
“…In our studies, total and free corticosterone levels were measured not only in the morning (9:00 a.m.) but also in the evening (9:00 p.m.) when the secretion of GC is at its peak (mice are nocturnal animals). In the morning, we found increased free GC levels in Cbg KO as in the study by Gulfo et al (29) or Petersen et al (28), but in the evening, this genotype difference was no longer present because the higher total GC levels in WT compensated the increased free GC percentage in Cbg KO. Thus, the lack of genotype effect on mRNA expression in basal conditions is expected since when free GC are high (at night), there are no genotype differences in their levels.…”
Section: Dissecting Metabolic Alterations In Cbg-deficient Mouse Modelssupporting
confidence: 76%
See 2 more Smart Citations
“…CBG-deficient mice show lower total corticosterone levels and higher free corticosterone and ACTH 15 , and greater adrenal gland size 16 , i.e., they have an altered response to the HPA axis. In addition, the sexual dimorphism that elicits increased levels of total corticosterone in females with respect to males is eliminated by CBG deficiency 17,18 .…”
Section: Introductionmentioning
confidence: 99%